Решить показательное уравнение: 8*4^x-6*2^x+1=0

zaya46 zaya46    1   08.09.2019 04:20    2

Ответы
viper998 viper998  07.10.2020 00:11
8*4^{x}-6*2^{x}+1=0 \\ 8*(2^{2})^{x}-6*2^{x}+1=0 \\ 8*(2^{x})^{2}-6*2^{x}+1=0
представим t=2^{x} \\ 8t^{2} -6t +1=0 \\ D=36-4*8=36-32=4=2^{2} \\ t_1= \frac {6+2}{16} =\frac {8}{16} = \frac {1}{2} \\ t_2= \frac {6-2}{16}=\frac {4}{16}=\frac {1}{4} \\ 2^{x}= \frac {1}{2} \\ 2^{x}=2^{-1} \\ x_1=-1 \\ 2^{x}= \frac {1}{4} \\ 2^{x}=2^{-2} \\ x_2=-2
ПОКАЗАТЬ ОТВЕТЫ
максим1715 максим1715  07.10.2020 00:11
8*4^x-6*2^x+1=0

Замена:
2^x=t \\ \\ 8t^2-6t+1=0 \\ \frac{D}{4}=9-8=1 \\ t_1= \dfrac{3+1}{8} = \dfrac{1}{2} \\ t_2= \dfrac{3-1}{8}= \dfrac{1}{4}

Обратная замена:
2^x= \dfrac{1}{2} \\ 2^x=2^{-1} \\ x=-1 \\ \\ 2^x= \dfrac{1}{4} \\ 2^x=2^{-2} \\ x=-2

ответ: -2; -1
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра

Популярные вопросы